Pengaruh Umur Sukuk, Ukuran Perusahaan, Dan Profitabilitas Terhadap Peringkat Obligasi Syariah (Sukuk) (Studi Empiris Pada Perusahaan Yang Menerbitkan Sukuk Di Bursa Efek Indonesia Periode 2012-2014) - Saputro, Nando; , Dr. Rini Kuswati, S.E., M.Si (2016)
Bonds are useful to investors and issuers to provide information regarding the company's ability to repay the bond debt. This study aims to determine the financial and non-financial factors that influence the rating of Islamic bonds. Independent variables in this study are: (1) Sukuk Maturity (2) Firm Size (3) Profitability. Samples were companies that issue sukuk bonds listed on the Indonesia Stock Exchange (BEI) and rated by PT PEFINDO. Criteria for sample using purposive sampling method. The total samples collected are 10 bonds from 6 go public companies. Hypothesis testing using ordinal regression analysis as the dependent variable in the form of an ordinal scale (rating). The results showed that the independent variables sukuk maturity, and Firm size has an influence on the rating of Islamic bonds at the 0.05 level. However, the profitability of the independent variable has no effect on the rating of Islamic bonds.